Early functional and radiological outcome between plaster cast and fibreglass cast in stable thoracolumbar burst fracture - Zakaria@Mohamad, Zamzuri; Sharifudin, Mohd Ariff; Ahmad Damen, Mohd Fairuz (2017)
Background: Burst fracture result from compression failure of both the anterior and middle column under substantial axial loads. Conservative treatment was a method of treatment for fractures without neurological deficit.